Nucleic Acid Transfection - Bielke, Wolfgang; Erbacher, Christoph (Topics in Current Chemistry, 2010)
Gene Delivery into Mammalian Cells: An Overview on Existing Approaches Employed In Vitro and In Vivo, by Peter Hahn and Elizabeth Scanlan * Strategies for the Preparation of Synthetic Transfection Vectors, by Asier Unciti-Broceta, Matthew N. Bacon, and Mark Bradley * Cationic Lipids: Molecular Structure/Transfection Activity Relationships and Interactions with Biomembranes, by Rumiana Koynova and Boris Tenchov * Hyperbranched Polyamines for Transfection, by Wiebke Fischer, Marcelo Calderon, and Rainer Haag * Carbohydrate Polymers for Nonviral Nucleic Acid Delivery, by Antons Sizovs, Patrick M. McLendon, Sathya Srinivasachari, and Theresa M. Reineke * Cationic Liposome-Nucleic Acid Complexes for Gene Delivery and Silencing: Pathways and Mechanisms for Plasmid DNA and siRNA, by Kai K. Ewert, Alexandra Zidovska, Ayesha Ahmad, Nathan F. Bouxsein, Heather M. Evans, Christopher S. McAllister, Charles E. Samuel, and Cyrus R. Safinya * Chemically Programmed Polymers for Targeted DNA and siRNA Transfection, by Eveline Edith Salcher and Ernst Wagner * Photochemical Internalization: A New Tool for Gene and Oligonucleotide Delivery, by Kristian Berg, Maria Berstad, Lina Prasmickaite, Anette Weyergang, Pål K. Selbo, Ida Hedfors, and Anders Høgset * Visualizing Uptake and Intracellular Trafficking of Gene Carriers by Single-Particle Tracking, by N. Ruthardt and C. Bräuchle.